Developing a UML to OWL conversion model for semantic web based application development - Mehrolhassani, Moein; Elci, Atilla (My University, 2009)
The purpose of this paper is to present an approach to develop ontology based applications for semantic web using OWL [9] ontologies derived UML [19]. Description logic based ontology languages such as OWL are usually defined in terms of an abstract (text-based) syntax and most care is spent on the formal semantics. The absence of a visual syntax has lead to propose a particular visual notation for the classic description logic. Conversion from UML to OWL should be done in a very precise way because it is not as straightforward as it seems. It is quite likely that there are multiple alternatives in OWL for representing of elements of the same UML construct and we would probably need best practices for the same. The study will devise a straightforward standard approach for converting UML diagrams to OWL to be used by developing tools to produce an ontology based application.
2009 International Conference on Enterprise Information Systems and Web Technologies, EISWT 2009 --
Keywords: Best practices; Conversion model; Description logic; Formal Semantics; Ontology language; Ontology-based applications; Visual notations; Visual syntaxes; Abstracting; Formal languages; Information systems; Syntactics; Data description